Interactive e-comic based on traditional games as a disaster mitigation educational media for elementary school students - Ady Darmansyah; Hadi Hardiansyah; Intan Dewi Kusuma; Khaeru Nasihin; Nady Febri Ariffiando; Atika Susanti (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2025)
Indonesia is a disaster-prone country; however, disaster mitigation education in elementary schools remains limited in innovation and less engaging for students. This study aims to develop an Interactive E-Comic based on traditional games as an educational medium for disaster mitigation for elementary school students. The research employed a Research and Development (R&D) method using an adapted Borg & Gall development model. The research subjects consisted of material experts, media experts, one teacher, and 30 fourth-grade students of SDN Kunciran 4 Tangerang. Data were collected through expert validation, teacher and student response questionnaires, and an effectiveness test on disaster mitigation knowledge. The validation results showed an average score of 15.5 from the material expert (very feasible category) and 11.5 from the media expert (feasible category). The teacher’s response to the media obtained a score of 74 (feasible), while students’ responses reached an average score of 15.15 (very feasible). The operational trial indicated an increase in students’ disaster mitigation knowledge, from an average pretest score of 48.20 to a posttest score of 82.50, with an N-gain of 0.66 (medium category). These findings indicate that the Interactive E-Comic based on traditional games is effective in improving students’ understanding of disaster mitigation and can serve as an engaging and contextual learning medium.